A positive feedback strategy for enhanced chemotherapy based on ROS-triggered self-accelerating drug release nanosystem. (June 2017) - Hu, Jing-Jing; Lei, Qi; Peng, Meng-Yun; Zheng, Di-Wei; Chen, Yi-Xuan; Zhang, Xian-Zheng
Abstract: Here, a positive feedback strategy was utilized to amplify the concentration of intracellular reactive oxygen species (ROS) and a ROS-triggered self-accelerating drug release nanosystem (defined as T/D@RSMSNs) was demonstrated for enhanced tumor chemotherapy. The mesoporous silica nanoparticles (MSNs) based nanocarriers were gated by β-cyclodextrin (β-CD) through the ROS-cleavable thioketal (TK) linker to encapsulate the anticancer drug doxorubicin hydrochloride (DOX) and ROS producing agent α-tocopheryl succinate (α-TOS), whose surface was further anchored with adamantane conjugated poly(ethylene glycol) chain (AD-PEG) via host-guest interaction. It was found that in human breast cancer (MCF-7) cells, T/D@RSMSNs could not only release DOX and α-TOS initiatively, but also lead to increased concentration of intracellular ROS, which could be used as new trigger to cut away TK linkage and then in turn facilitate the further release of DOX for enhanced chemotherapy. Both in vitro and in vivo experiments demonstrated that T/D@RSMSNs exhibited more significant antitumor activity in the human breast cancer than the traditional single-DOX loaded ROS-responsive nanocarrier. This novel ROS-triggered self-accelerating drug release nanosystem with remarkably improved therapeutic effects could provide a general strategy to branch out the applications of existing ROS-responsive drug delivery systems (DDSs). Graphical abstract: